Fermentation of Glycerol from Biodiesel Waste to 1,3-Propanediol - Dewi Anggraini (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
One of the most valuable products in chemical industry is 1,3-Propanediol (1,3-PD) because it has numerous applications for the production of polymers, cosmetics, foods, medicines, and lubricants. 1,3-PD production can be synthesized with chemical and fermentation method. Chemical method requires high pressure and temperature as well as catalysts are expensive. 1,3-PD production with fermentation method from crude glycerol as by-product of the biodiesel is promising, because it will increase the economic value of the crude glycerol beside the process is less expensive and eco friendly. In this study, crude glycerol was used as a raw material and Enterobacter aerogenes as inoculum in the fermentation process. First crude glycerol was purified using H3PO4 into pH 2 and then neutralized with NaOH. It was continued with bleaching process using activated carbon and water evaporation to obtained glycerol with high purity. Various fermentation process variables such fermentation time, temperature of fermentation, and amount of inoculum were studied. Crude glycerol, purified glycerol, and fermentation results were analyzed by Gas Chromatography (GC) to obtained the purity. Glycerol from purification result had achieved commercial glycerol standard. The best fermentation result was obtained at 1 day of fermentation with purity of 1,3-PD was 46.0685% ; temperature of 25 oC with purity of 1,3-PD was 51.2461% ; and 7% volume of inoculum with purity of 1,3-PD was 31.5919%.